Rancang Bangun Sistem Otomatisasi Suhu Dan Monitoring pH Air Aquascape Berbasis IoT (Internet Of Thing) Menggunakan Nodemcu Esp8266 Pada Aplikasi Telegram - Dendy Ramdani (Journal of INISTA, 2020)
Aquascape or artificial ecosystem in the aquarium has a high level of sensitivity in terms of maintenance, various factors that need to be considered, including temperature, and the level of acidity (pH) in the water. The design and construction of temperature automation and pH monitoring tools is based on the problem of aquascape owners who must regularly pay attention to temperature and pH stability at all times for the survival of the aquascape ecosystem. In this research and design, the DS18B20 sensor is used to detect temperature and the pH Detection Sensor Module to detect the acidity level of the water. The sensors are connected to the Nodemcu ESP8266 series microcontroller as in this study the microcontroller is programmed using the Arduino IDE with the specified parameters, the water temperature of the aquascape is 25°C-28°C and a pH value between 6.0-8.0. The result of the automation of this tool is that if the temperature sensor states a value of less than 25°C, the lights will automatically turn on and vice versa if the sensor detects a temperature of more than 28 ° C, the cooling fan will turn on. From the results of monitoring the pH of aquascape water on a telegram bot, if the pH is <6 or> 8 then nodemcu will immediately send a warning message notification that the water pH is too low or the water pH is too high. This study uses the NTP Client Server which functions as a lighting schedule for the aquascape lamp for 8 hours per day.